The impact of multiple myeloma drugs treatments on autologous stem cell transplantation in the era of new drugs - Wan, Xixi; Yu, Tian; Yu, Tao; Cai, Huili (Frontiers in Oncology, 2025)
Autologous stem cell transplantation (ASCT) is the standard treatment recommended by the National Comprehensive Cancer Network (NCCN) for newly diagnosed multiple myeloma (MM) patients who are eligible for transplantation. This procedure follows response achieved through induction therapy. The key to the success of ASCT lies in the quantity and quality of hematopoietic stem cells collected after mobilization. Studies have shown a positive correlation between the number of hematopoietic stem cells collected and the engraftment time of absolute neutrophil count (ANC) and platelet count (PLT). However, the advent of novel therapeutic agents that have significantly improved the survival of MM patients has also impacted hematopoietic stem cell mobilization, potentially delaying hematopoietic recovery, a process referred to as hematopoietic remodeling. In this paper, we will retrospectively analyze and summarise the research progress related to the effects of previous chemotherapeutic agents on hematopoietic stem cell mobilization and hematopoietic remodeling, to further improve the prognosis and quality of survival of MM patients who are eligible for transplantation.